1999
DOI: 10.1046/j.1523-1755.1999.07134.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin inhibitors enhance low-density lipoprotein oxidation in transplant patients

Abstract: Calcineurin inhibitors enhance low-density lipoprotein oxida-complexes with their respective immunophilins and tion in transplant patients.these complexes then inhibit a key enzyme serine/threo-Background. Our objective was to assess the pro-oxidant nine phosphatase, calcineurin, which is involved in the status of neoral and tacrolimus in renal transplant patients and dephosphorylation of the transcription factor NFA-T. monitor the protection provided by vitamin C and vitamin E in normalizing low density lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…Several mechanisms may be involved in the oxidant effects of these drugs. Both drugs have been reported to increase the oxidability of LDL particles [7, 8, 29]. In animal models, the metabolisms of calcineurin inhibitors are accompanied by increased free ROS, with a concomitant increase in levels of MDA, an end product of lipid peroxidation [30, 31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several mechanisms may be involved in the oxidant effects of these drugs. Both drugs have been reported to increase the oxidability of LDL particles [7, 8, 29]. In animal models, the metabolisms of calcineurin inhibitors are accompanied by increased free ROS, with a concomitant increase in levels of MDA, an end product of lipid peroxidation [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the acute and chronic nephrotoxicities of both drugs limit their beneficial effects [5, 6]. Both drugs are reported to enhance oxidative stress and augment atherosclerosis by increasing the oxidizability of low-density lipoprotein (LDL) particles [7, 8]. Yet the data are controversial as there are inconsistent reports indicating unaltered [9] or improved oxidative stress following kidney transplantation [10, 11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concomitant administration of FK506 and Vitis vinifera L promoted a significant reduction in the levels of urinary peroxides and improved renal function, observed by the increase of creatinine clearance. Another study showed the pro-oxidant action of calcineurin inhibitors through lipid peroxidation and confirmed the renoprotective effects of the use of vitamins A and C, both antioxidants (24) . The renoprotective effects afforded by Vitis vinifera L may be related to scavenging free radicals, inhibition of lipid peroxidation, or even its action in both pathways.…”
Section: Discussionmentioning
confidence: 76%
“…26 Even though the prooxidant activities of Tac and CyA have been intensively studied, a large number of contradictory results have been published. Some authors consider CyA to be a more potent prooxidant than Tac, 27 but other studies have not confirmed these findings. 7 Our results showed that there were no significant differences between effects of CyA and Tac on OS-related parameters after transplantation.…”
Section: The Effect Of Immunosuppressivesmentioning
confidence: 97%